An empirical research on management innovation of high-technology manufacturers. (30th June 2015) - Huang, Po-Yu; Wu, Tian-Sheng; Chen, Li-Jia; Saito, Riga; Yu, Chih-Lang; Huang, Chih-Yao; Tsai, Sang-Bing; Xue, You-Zhi; Chen, Quan; Chen, Chang-Bin; Wang, Jiang-Tao; Tang, Ling
Management innovation is the method with which enterprises acquire competitive advantage over their competitors, especially in current fierce competitive industry environment. Simultaneous importance–performance analysis can be used to simultaneously analyze three concepts of management innovation factors including the importance, self-expression, and the performance of competitors, so that enterprises are able to understand the status of their management innovation capability. Decision-making trial-and-evaluation laboratory is the method for enterprises to process and calculate the level of influence and causality between the indicators and subsequently determine the weight of the indicators. This study developed the 14 management innovation–based assessment indicators to evaluate a management innovation capability. In the first stage, simultaneous importance–performance analysis is used to compare the management innovation capabilities of company A and its competitors. In the second stage, decision-making trial-and-evaluation laboratory is used to analyze the influence and causality between the indicators. Finally, the strategies of management innovation are rebuilt based on the simultaneous importance–performance analysis and decision-making trial-and-evaluation laboratory analysis, which has both theoretical and practical contributions.